Opioids and breast cancer recurrence: A Danish population‐based cohort study - Cronin‐Fenton, Deirdre P.; Heide‐Jørgensen, Uffe; Ahern, Thomas P.; Lash, Timothy L.; Christiansen, Peer M.; Ejlertsen, Bent; Sjøgren, Per; Kehlet, Henrik; Sørensen, Henrik T. (Cancer, 2015)
BACKGROUND Opioids may alter immune function, thereby potentially affecting cancer recurrence. The authors investigated the association between postdiagnosis opioid use and breast cancer recurrence. METHODS Patients with incident, early stage breast cancer who were diagnosed during 1996 through 2008 in Denmark were identified from the Danish Breast Cancer Cooperative Group Registry. Opioid prescriptions were ascertained from the Danish National Prescription Registry. Follow‐up began on the date of primary surgery for breast cancer and continued until breast cancer recurrence, death, emigration, 10 years, or July 31, 2013, whichever occurred first. Cox regression models were used to compute hazard ratios and 95% confidence intervals associating breast cancer recurrence with opioid prescription use overall and by opioid type and strength, immunosuppressive effect, chronic use (≥6 months of continuous exposure), and cumulative morphine‐equivalent dose, adjusting for confounders. RESULTS In total, 34,188 patients were identified who, together, contributed 283,666 person‐years of follow‐up. There was no association between ever‐use of opioids and breast cancer recurrence (crude hazard ratio, 0.98; 95% confidence interval, 0.90‐1.1; adjusted hazard ratio, 1.0; 95% confidence interval, 0.92‐1.1), regardless of opioid type, strength, chronicity of use, or cumulative dose. Breast cancer recurrence rates were lower among users of strongly (but not weakly) immunosuppressive opioids, possibly because of channeling bias among those with a high competing risk, because mortality was higher among users of this drug type. CONCLUSIONS This large, prospective cohort study provided no clinically relevant evidence of an association between opioid prescriptions and breast cancer recurrence. The current findings are important to cancer survivorship, because opioids are frequently used to manage pain associated with comorbid conditions. Cancer 2015;121:3435–43. © 2015 American Cancer Society. The association between opioid prescriptions and breast cancer recurrence is investigated. The findings indicate no evidence of an effect of opioids on breast cancer recurrence in a cohort of 34,188 patients with early stage breast cancer in Denmark.